Uma análise da política fiscal de repasse de ICMS no desempenho educacional dos municípios cearenses no período de 2012 a 2014 - Santos, Francisca Fabiana dos (2017)
This paper proposes to analyze the fiscal policy of transfer of ICMS to the municipalities of Ceará on their respective levels of educational performance. We use a panel database in which the cross-sectional units are tracked over time. Having as a dependent variable a measure of educational performance and as explanatory the municipal public expenditures per student in education, the number of students per classroom, the rate of teachers with higher education and the Gross Domestic Product per capita of the municipalities. The results suggest that the transfer volume of the ICMS Share Quotient is related to the school performance of the students of the municipal public school system, however, it has a greater impact in the initial classes of primary education than in the final.